The Matchmaker Exchange API: Automating Patient Matching Through the Exchange of Structured Phenotypic and Genotypic Profiles. Issue 10 (17th September 2015) - Buske, Orion J.; Schiettecatte, François; Hutton, Benjamin; Dumitriu, Sergiu; Misyura, Andriy; Huang, Lijia; Hartley, Taila; Girdea, Marta; Sobreira, Nara; Mungall, Chris; Brudno, Michael
<x xml:space="preserve">Abstract</x> The Matchmaker Exchange API defines a protocol and data format for exchanging phenotype and genotype profiles between patient databases, in order to facilitate the identification of additional cohorts and increase the rate with which rare diseases can be researched and diagnosed. The API is straightforward and flexible in order to simplify its adoption on a large number of data types and workflows.